La gestión administrativa y su incidencia en el riesgo laboral en la empresa Pismade s.a, 2017 - Molina Bayas, Pamela Alejandra (2018)
This study aims to demonstrate that the administrative management influences the occupational risk in PISMADE SA, Company in 2017. A strategic plan is presented, it will be very helpful so that the company improves its administrative management in a technical way, to prevent internal accidents and occupational risks. First chapter: It is composed of the referential framework, which integrates the problem statement, problem formulation, general and specific objectives. Second Chapter: Consists of the theoretical framework, which contains background and the theoretical foundation. The first unit that covers the generalities of the PISMADE SA Company, second unit refers to administrative management and finally the third unit as regards labor risk. Third Chapter: The methods used in this investigation are detailed, the type of research, the design of the population and sample research, the techniques and instruments for gathering information, the processing of information, the analysis and interpretation of results. Fourth Chapter: It is composed of the conclusions and recommendations of the investigation, finally it will be possible to demonstrate the results to the problems posed at the beginning of the investigation. Fifth Chapter: This chapter is compound of the proposal of the theme, which consists in approaching new strategies that can avoid any risk in the human talent of the PISMADE SA Company. This chapter details in a clear and concise way the objective, the cost per collaborator and for all the members, setting the time that will be carried out, the responsible person and the indicators.